How to choose a progestogen for hormone therapy of the menopausal period? - Pertyński, Tomasz; Stachowiak, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2008)
The choice of a proper progestogen for hormone therapy (HT) of the menopausal period, including its dosage and route of administration, is a crucial element of so-called tailored therapy. Remembering all the indications and contraindications for this kind of treatment one should know that progestogens used in HT are a big group of compounds with different affinity for the receptors – progesterone, estrogen, androgen, mineral- and glucocorticoid – what results in different, in many cases even opposed, final metabolic effects. This knowledge allows to choose the best possible form of progestogen therapy and to avoid, or minimize, some side-effects connecting with this kind of hormone administration.